MEASURING THE USER EXPERIENCE OF THE SATUSEHAT APPLICATION WITH THE HEART METRICS METHOD APPROACH - Antonius Alijoyo, Franciskus; Suhaerudin, Suhaerudin; Meilia, Safina (Penerbit Lafadz Jaya, 2024)
Satu Sehat application is a transformation of the Peduli Lindungi application as an important innovation step in an effort to utilise information technology to improve the quality of health services. This study aims to measure user satisfaction or user experience of the SatuSehat application using the HEARTMetric method so as to analyse the application from the point of view of user experience satisfaction which includes Happines, Engagment, Adoption, Retention and Task Success. Data collection was carried out by simple random sampling with respondents used in this research sampling test were 140 respondents. After the data is collected, the validity and reliability of the statement items are tested and analysed using Importance Performance Analysis. Based on the results of the analysis, the main priority that needs to be done is to increase and improve the quality of the Happiness variable. OneHealth application developers need to develop features that make it easier for users, innovate features and socialise the use of application features.